CHARACTERISTICS OF BIOBRIQUETTE FROM ARECA NUT WASTE AND COCONUT WASTE WITH VARIOUS TYPES AND PROPORTION OF BINDERS - Yulia, Ade; Yernisa, Yernisa; Fiardilla, Fauziah (LPPM Universitas Jambi, 2026)
Biobriquettes derived from agricultural waste such as coconut shells, coconut husks, and areca husks offer potential as renewable energy sources. This study aimed to evaluate the effect of binder type and proportion on the quality of biobriquettes in accordance with the Indonesian National Standard (SNI). The raw materials consisted of 30% coconut shell charcoal, 30% coconut husk charcoal, and 30% areca husk charcoal, combined with three organic binders: tapioca starch, cornstarch, and hibiscus leaf extract. A completely randomized design (CRD) was applied with variations in binder type and proportion. The briquettes were analyzed for moisture content, ash content, volatile matter, burning rate, density, and calorific value. Data were statistically evaluated using one-way ANOVA followed by Duncan’s New Multiple Range Test (DNMRT) at 5% and 1% significance levels. The results showed that binder type and proportion significantly affected calorific value, volatile matter content, burning rate, and density, while moisture and ash content were more influenced by raw material characteristics and carbonization process. The findings indicate that binders not only function as mechanical adhesives but also influence combustion behavior and structural properties. Most quality parameters met international standards, although the calorific value did not fully comply with SNI requirements. The novelty of this study lies in the balanced combination of three biomass charcoals and the simultaneous comparative evaluation of three organic binders within one compositional system. These results support the optimization of binder formulation to enhance performance, so that biobriquettes can be developed as a renewable alternative energy source.